Enhancing decision making by providing a unified system for computer-interpretable guideline management - Ferreira da Silva, Alexandre (2021)
The need for integration of clinical practice guidelines (CPGs) in daily clinical practice calls for computational systems able to operationalise their knowledge and provide an enhanced experience in their enactment. Current approaches lack in functionalities such as scheduling and temporal management of CPGs, the combination of CPGs, and user-friendly systems for computer-interpretable guideline (CIG) creation and editing. This paper presents a comprehensive architecture for the deployment of CIGs, featuring components that allow the following: the creation and manipulation of clinical practice guideline knowledge elements, execution of CIGs with the temporal verification of clinical tasks, and drug conflict identification and resolution. This comprehensive approach provides a step-by-step assistant for health care professionals in the form of an agenda of activities that detects drug interactions when they are prescribed simultaneously and applies a mitigation algorithm to select possible and conflict-free alternatives. This work addresses the lack of a unified pipeline and mitigation features shown in approaches to CIG conflict mitigation in use.